Exploring Psychological Well-being as Determinant of Savings and Investment Behaviour among Civil Servants in Plateau State, Nigeria - Damilep, Jonah Zumlong; Ajiji, Tessy; Yohanna, Panshak (NIU Journal of Social Sciences, 2026)
The study explored psychological well-being as determinant of savings and investment behaviour among civil servants in Plateau State, Nigeria utilizing 275 participants (138 males and 137 females) with ages from 19 to 59 years drawn from Ministries, Departments and Agencies. Purposive sampling and cross-sectional design were utilized, and hypotheses tested using multiple regression analyses at 0.05 level of significance. Findings revealed none of the psychological well-being dimensions significantly predicted savings behaviour among the participants. Specifically, autonomy (β = .002, t = .031, p > .05), environmental mastery (β = –.010, t = –.144, p > .05), personal growth (β = –.105, t = –1.393, p > .05), positive relations with others (β = –.087, t = –1.053, p > .05), purpose in life (β = .095, t = 1.316, p > .05), and self-acceptance (β = .052, t = .631, p > .05). Furthermore, only one dimension of psychological well-being (environmental mastery) significantly predicted investment behaviour among the participants. Specifically, autonomy (β = –.089, t = –1.218, p > .05), environmental mastery (β = –.201, t = –2.897, p < .05), personal growth (β = –.041, t = –.557, p > .05), positive relations with others (β = –.080, t = –.989, p > .05), purpose in life (β = .093, t = 1.313, p > .05), and self-acceptance (β = .114, t = 1.406, p > .05). This study concluded that none of psychological well-being dimension significantly predicted savings behaviour, but environmental mastery significantly predicted investment behaviour among participants.   Keywords: Psychological Well-being, Savings Behaviour, Investment Behaviour, Civil Servants, Plateau State.